2015
DOI: 10.1371/journal.pone.0126927
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors of Korean Gastric Cancer Survivors with Hypertension: A Propensity Analysis of KNHANES III-V (2005–2012)

Abstract: ObjectiveThis study provides a comparison of health behaviors between gastric cancer survivors with hypertension and non-cancer subjects in Korea.MethodsData from the Korean National Health and Nutrition Examination Survey (KNHANES) for the period of 2005-2012 were used in this study. A propensity score matching method was used to compare health behaviors. Before the matching of propensity scores, the number of participants was 11034 (102 gastric cancer survivors and 10932 non-cancer participants). A 1:5 prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Similarly, previous studies have shown that a high percentage (66.3%) of patients with GC is smokers ( Okada et al, 2017 ) and that 48% of PC patients are current or previous smokers ( Keane et al, 2014 ). Further studies have reported that PC is not affected by smoking (OR=0.60, 95% CI: 0.30~1.19, P =0.141) ( Jo et al, 2015 ), and that active and passive smoking may play an important role in the development of cardial stomach cancer ( Mao et al, 2002 ). However, Duan et al (2009) did not report any evidence that passive smoking had any appreciable effect on oesophageal or gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have shown that a high percentage (66.3%) of patients with GC is smokers ( Okada et al, 2017 ) and that 48% of PC patients are current or previous smokers ( Keane et al, 2014 ). Further studies have reported that PC is not affected by smoking (OR=0.60, 95% CI: 0.30~1.19, P =0.141) ( Jo et al, 2015 ), and that active and passive smoking may play an important role in the development of cardial stomach cancer ( Mao et al, 2002 ). However, Duan et al (2009) did not report any evidence that passive smoking had any appreciable effect on oesophageal or gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…However, cancer survivors are considered to engage in better hypertension management behavior than the general population [ 45 ]. Cancer survivors are also more likely to be aware of, treat, and manage high blood pressure, and have better access to knowledge on health-improving behaviors such as vaccination or cancer screening, improvements in nutrition and exercise, and reduction or cessation of smoking and drinking [ 46 , 47 ]. This may explain our finding that a history of hypertension is associated with a decreased mortality rate.…”
Section: Discussionmentioning
confidence: 99%